2011
DOI: 10.5491/shaw.2011.2.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-sized Carbon Black Particles on Lung and Circulatory System by Inhalation Exposure in Rats

Abstract: ObjectivesWe sought to establish a novel method to generate nano-sized carbon black particles (nano-CBPs) with an average size smaller than 100 nm for examining the inhalation exposure risks of experimental rats. We also tested the effect of nano-CBPs on the pulmonary and circulatory systems.MethodsWe used chemical vapor deposition (CVD) without the addition of any additives to generate nano-CBPs with a particle size (electrical mobility diameter) of less than 100nm to examine the effects of inhalation exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Overall, we found a single exposure to relevant doses of spark-generated AgNP and CNP to have low toxic effects on human bronchial epithelia. These findings are coherent with data from many rodent inhalation studies and a few studies in vitro showing no statistically significant cellular response after application of realistic NP doses [ 52 , 53 , 54 , 55 , 56 , 57 ]. Many other published in vitro studies, however, administered unrealistically high AgNP and CNP doses to achieve significant acute toxicity [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Effects Of Selected Commercial Enp On Normal and Diseasesupporting
confidence: 88%
“…Overall, we found a single exposure to relevant doses of spark-generated AgNP and CNP to have low toxic effects on human bronchial epithelia. These findings are coherent with data from many rodent inhalation studies and a few studies in vitro showing no statistically significant cellular response after application of realistic NP doses [ 52 , 53 , 54 , 55 , 56 , 57 ]. Many other published in vitro studies, however, administered unrealistically high AgNP and CNP doses to achieve significant acute toxicity [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Effects Of Selected Commercial Enp On Normal and Diseasesupporting
confidence: 88%
“…In contrast, there was no evidence for toxic changes after 28 and 90 days of AgNP inhalation in rats (Hyun et al, 2008;Ji et al, 2007;Kim et al, 2011b). Similarly, inhalation studies with CNP in rats revealed only mild inflammatory and oxidative stress responses (Kim et al, 2011a;Li et al, 1999). The substantially higher toxicity of AgNP and CNP found by in vitro studies is likely due to extreme and unrealistically high concentrations of suspended NP (450 mg/mL) applied to submerged cells, and exposing the cells to all particles at once.…”
Section: Introductionmentioning
confidence: 82%
“…For example, inhalation of CB particles with a diameter of 83.3-87.9 nm for 4 weeks neither induced toxicity of the rat’s lungs nor elicited most of pulmonary pro-inflammatory cytokines. The histological analysis further revealed that nanoscale CB particles did not induce inflammatory responses in the respiratory system [ 42 ]. Another study indicated that a short-time inhalation of nanoscale CB particles at 10 mg/m 3 could not induce changes of IL-6, IL-8, and TNF-α in rat [ 43 ].…”
Section: Discussionmentioning
confidence: 99%